Factors associated with employees' choice of mandatory retirement plan: the case of Malaysian public universities - Tolos, Habibah; Abu Bakar, Arpah; Yusuf, Muhammad Bashir Owolabi (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2014)
This study examines the factors that influence public sector employees in making a decision to enroll in either one of the two types of mandatory retirement plans.A survey of 348 Malaysian public universities employees was conducted, and the data obtained were analyzed using a logistic regression model.The results show that knowledge, plan feature, sources of retirement income, health status, job mobility, and extending work are the contributing factors of the choice of the retirement plan.Apart from extending the extant literature on retirement plan, this study provides further understanding of the employees' retirement decision in a different scenario of retirement systems.